Zur Synonymie von Leucophlebia lineata brunnea Closs nebst Bemerkungen zu einigen Sphingiden aus Sauters Formosa-Ausbeute in der Sammlung des Deutschen Entomologischen Institutes (Lepidoptera: Sphingidae). - Riotte, J. C. E. (Contributions to Entomology = Beiträge zur Entomologie, 1968)
Four species of Formosan Sphingids (Lepidoptera), collected by Sauter, preserved in the collection of the German Entomological Institute, and reviously discussed by Closs (1915) were inspected and re-determined. Leucophlebia lineata brunnea Closs (1915) has priority over Leucophlebia lineata formosana B.P. Clark (1936). Nomenclatural Acts formosana Clark, 1936 (Leucophlebia lineata), syn. n. of Leucophlebia lineata brunnea Closs, 1915